Risk Factors of Urinary Tract Infections Caused by Extended-Spectrum Î’-Lactamase-Producing Escherichia Coli in Inpatients at a Tertiary Hospital in Surabaya, Indonesia - Wuwuti, Ishak Samuel; , Kuntaman; Wasito, Eddy Bagus (Folia Medica Indonesiana, 2022)
Highlights: • ESBL frequency in women was higher than in men. • Catheter use in patients with urinary tract infections and recurrent urinary tract infections has four times the risk of ESBL caused by Escherichia coli bacteria • ESBL-producing E.coli bacteria are resistant to amoxicillin-clavulanic, ceftazidime, aztreonam, and ceftriaxone. Abstract: The incidence of urinary tract infections (UTIs) caused by extended-spectrum beta-lactamase (ESBL) producing Escherichia coli (E. coli) bacteria has become a global problem and has increased in recent years. The purpose of this study was to analyze the risk factors for the incidence of UTI in inpatients at Dr. Soetomo General Academic Hospital Surabaya. This research was an analytic descriptive study. Specimens were sent to the Clinical Microbiology Laboratory using sterile containers and processed according to standard laboratory procedures. It resulted in ESBL-producing E. coli that were used as a case group and non ESBL-producing E. coli as a control group. The identification and testing of antibiotic susceptibility were carried out using the BD Phoenixâ„¢ Automated Microbiology System. Ninety-four bacterial isolates were collected, consisting of 54 (57.4%) ESBL-producing E. coli bacteria and 40 (42.6%) non ESBL-producing E. coli bacteria. Recurrent UTIs (OR = 4.31; Ï =0.002; 95% CI = 1.68-11.04) and catheter use (Ï = 0.049; OR = 4.250; 95% CI = 1.050-17.210) were used as independent risk factors caused by ESBL-producing E. coli bacteria. Recurrent UTIs and catheter use were dependent risk factors caused by ESBL-producing E. coli bacteria.